Detection of elevated right ventricular extracellular volume in pulmonary hypertension using Accelerated and Navigator-Gated Look-Locker Imaging for Cardiac T1 Estimation (ANGIE) cardiovascular magnetic resonance. Issue 1 (December 2015) - Mehta, Bhairav; Auger, Daniel; Gonzalez, Jorge; Workman, Virginia; Chen, Xiao; Chow, Kelvin; Stump, Claire; Mazimba, Sula; Kennedy, Jamie; Gay, Elizabeth; Salerno, Michael; Kramer, Christopher; et al.
Abstract Background Assessment of diffuse right ventricular (RV) fibrosis is of particular interest in pulmonary hypertension (PH) and heart failure (HF). Current cardiovascular magnetic resonance (CMR) T1 mapping techniques such as Modified Look-Locker inversion recovery (MOLLI) imaging have limited resolution, but accelerated and navigator-gated Look-Locker imaging for cardiac T1 estimation (ANGIE) is a novel CMR sequence with spatial resolution suitable for T1 mapping of the RV. We tested the hypothesis that patients with PH would have significantly more RV fibrosis detected with MRI ANGIE compared with normal volunteers and patients having HF with reduced (LV) ejection fraction (HFrEF) without co-existing PH, independent of RV dilitation and dysfunction. Methods Patients with World Health Organization group 1 or group 4 PH, patients with HFrEF without PH, and normal volunteers were recruited to undergo contrast-enhanced CMR. RV and LV extracellular volume fractions (RV-ECV and LV-ECV) were determined using pre-contrast and post-contrast T1 mapping using ANGIE (RV and LV) and MOLLI (LV only). Results Thirty-two participants (53.1 % female, median age 52 years, IQR 26–65 years) were enrolled, includingn  = 12 with PH, n  = 10 having HFrEF without co-existing PH, andn  = 10 normal volunteers. ANGIE ECV imaging was of high quality, and ANGIE measurements of LV-ECV were highly correlated with those of MOLLI (r  = 0.91;p  < 0.001). The RV-ECV in PH patients was 27.2 % greater than the RV-ECV in normal volunteers (0.341 v. 0.268;p  < 0.0001) and 18.9 % greater than the RV-ECV in HFrEF patients without PH (0.341 v. 0.287;p  < 0.0001). RV-ECV was greater than LV-ECV in PH (RV-LV difference = 0.04), but RV-ECV was nearly equivalent to LV-ECV in normal volunteers (RV-LV difference = 0.002) (p  < 0.0001 for RV-LV difference in PH versus normal volunteers). RV-ECV was linearly associated with both increasing RVEDVI (p  = 0.049) and decreasing RVEF (p  = 0.04) in a multivariable linear model, but PH was still associated with greater RV-ECV even after adjustment for RVEDVI and RVEF. Conclusions Pre- and post-contrast ANGIE imaging provides high-resolution ECV determination for the RV. PH is independently associated with increased RV-ECV even after adjustment for RV dilatation and dysfunction, consistent with an independent effect of PH on fibrosis. ANGIE RV imaging merits further clinical evaluation in PH.